Rhizospheric bacteria with potential benefits in agriculture - Rodríguez-Sahagún, Araceli; Velasco-Jiménez, Antonio; Castellanos-Hernández, Osvaldo; Acevedo-Hernández, Gustavo; Clarenc Aarland, Rayn (REVISTA TERRA LATINOAMERICANA, 2020)
Rhizobacteria are a vast and diverse group of bacteria that live in the environs of the plant roots, which develop beneficial, neutral and even harmful relationships, although the latter to a lesser extent. The interactions between bacteria and plant roots rich in nutrients have played a decisive role in the adaptation and productivity of plants over time. Several studies show that rhizobacteria have improved the growth, the production and health of plants directly through mechanisms that include the assimilation of vital nutrients such as nitrogen and the facilitation of nutrients such as phosphorus, potassium, and phytostimulation through the production of various phytohormones; and indirectly affecting the growth of important phytopathogens, activating immunity in plants and lessen the problems caused by abiotic stress. Due to their metabolic diversity, rhizobacteria could positively contribute to the improvement of agricultural productivity and the solution of environmental problems caused by current agriculture. Different genera such as: Acidithiobacillus, Aminobacter, Arthrobacter, Azoarcus, Azospirillum, Azotobacter, Bacillus, Burkholderia, Clostridium, Enterobacter, Gluconoacetobacter, Pseudomonas, Serratia and Sphingomonas have demonstrated their enormous capacity to promote growth. This review provides a focus on the mechanisms by which rhizobacteria improve plant growth, their contribution to sustainable agriculture and their commercialization, a field that continues to grow steadily.